The social burden and quality of life of patients with haemophilia in Italy - Kodra, Yllka (Edizioni SIMTI - SIMTI Servizi Srl, 2014)
BACKGROUND: In Italy, the project on the social burden and quality of life (QoL) of patients with haemophilia investigates costs from a society perspective and provides an overview of their quality of life. Moreover, as life expectancy increased in recent years along with new treatment strategies implemented in the last decades, it analyses trends of costs other than drugs simulating impacts during patient whole life. MATERIAL AND METHODS: We ran a web-based cross-sectional survey supported by the Italian Federation of Haemophilia Societies in recruiting patients with haemophilia and their caregivers. We developed a questionnaire to collect information on demographic characteristics, healthcare and social services consumption, formal and informal care utilisation, productivity loss and quality of life. In particular, quality of life was assessed through the EuroQoL tool. Last, we applied the illness cost method from a society perspective. RESULTS: On average, quality of life is worse in adult patients compared to child and caregivers: more than 75% of adult patients declare physical problems, 43% of adult patients and 54% of their parents have anxiety problems. Assuming a society perspective, the estimated mean annual total cost per patient in 2012 is 117,732 €. Drugs represent 92% of total costs. Focusing on costs other than drugs, each additional point of EuroQoL tool implies a costs’ reduction of 279 €. The impact of age varies across age groups: each added year implies a total decrease of costs up to 46.6 years old. Afterwards, every additional year increases costs. DISCUSSION: Quality of life of patients with haemophilia and their caregivers improved and it influences positively on consumed resources and on their contribution to the social-economic system. Costs other than drugs for patients with haemophilia follow the same trends of general population.